Effect of the Snakes and Ladders Game on Increasing Knowledge about Food Safety of Snacks in Class V Students of SDI Level Oebobo 2 Kupang - Putri, Shanaz Rezky Tamara Rosari; Limbu, Ribka; Ndun, Helga J.N.; Nabuasa, Enggelina (Faculty of Public Health, Nusa Cendana University, 2023)
Knowledge of food safety snacks should be introduced to children as early as possible to prevent children from disease caused by unhealthy snackfood. Knowledge can be increased through health education using snake ladder game. The purpose of this study was to determine the influence of snakes and ladders on increasing knowledge about food safety for students in class V SDI Graded Oebobo 2 Kupang. The method used in this study was pre-experimental research design with one group pretest and posttest design. The sample consisted of 45 fifth grade students selected by applying total sampling techniques. The results showed that there was a difference between the mean of respondents' knowledge before treatment (59)and after treatment (86.33) with the significance value of ρ = 0,000 (ρ <α = 0.05). The snake and ladder game in this study can be a media used for increasing knowledge of school children about food safety.